2022
DOI: 10.3389/fimmu.2022.825834
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Preconditioning Modulates the Peripheral Innate Immune System to Promote Anti-Inflammatory and Protective Responses in Mice Subjected to Focal Cerebral Ischemia

Abstract: The development of tolerance triggered by a sublethal ischemic episode (preconditioning, PC) involves a complex crosstalk between neurons, astrocytes and microglia, although the role of the peripheral immune system in this context is largely unexplored. Here, we report that severe cerebral ischemia caused by transient middle cerebral artery occlusion (MCAo) in adult male mice elevates blood counts of inflammatory neutrophils and monocytes, and plasma levels of miRNA-329-5p. These inflammatory responses are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 140 publications
(200 reference statements)
0
8
0
Order By: Relevance
“…The blots were then incubated overnight at 4 °C, with the following primary antibodies: mouse anti-TSG-6 (1:1000; MABT108, Merck Millipore, Milan, Italy), rabbit anti-Ym1 (1:1000; 60130, StemCell Technologies, Meda, MB, Italy) and mouse anti-β-actin (1:3000; A3853, Sigma-Aldrich, Milan, Italy). This was then followed by incubation with the appropriate secondary antibodies (1:3000; Sigma-Aldrich, Milan, Italy) for 1 h at room temperature [ 13 ]. Immunodetection and quantification of protein bands were performed using the iBright™ FL1500 (Thermo Fisher Scientific, Monza, MB, Italy) and ImageJ software.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The blots were then incubated overnight at 4 °C, with the following primary antibodies: mouse anti-TSG-6 (1:1000; MABT108, Merck Millipore, Milan, Italy), rabbit anti-Ym1 (1:1000; 60130, StemCell Technologies, Meda, MB, Italy) and mouse anti-β-actin (1:3000; A3853, Sigma-Aldrich, Milan, Italy). This was then followed by incubation with the appropriate secondary antibodies (1:3000; Sigma-Aldrich, Milan, Italy) for 1 h at room temperature [ 13 ]. Immunodetection and quantification of protein bands were performed using the iBright™ FL1500 (Thermo Fisher Scientific, Monza, MB, Italy) and ImageJ software.…”
Section: Methodsmentioning
confidence: 99%
“…MicroRNA was extracted from plasma samples using a miRNeasy Serum/Plasma Kit (Qiagen, Inc., Hilden, Germany). Briefly, 5 volumes of QIAzol lysis reagent were added to plasma and 5 pM A. Thaliana miR-159a (478411_mir, Life Technologies, Monza, MB, Italy) was spiked into the mixture [ 13 ]. Subsequently, chloroform was mixed in the solution which was then centrifuged for 15 min at 12,000× g at 4 °C to obtain three layers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…216,217 While preconditioning responses occur in virtually all cells of the central nervous system, immune cells seem to play a particularly critical role because depleting microglia abolishes preconditioning responses. 218,219 Additionally, reduced inflammation and initiation of vascular remodeling have been described as components of the phenotypic response to preconditioning. 218 A recent study assessing the role of ischemic preconditioning on peripheral macrophages identified an elevated M2/M1 macrophage ratio in the brain following experimental ischemic injury, as well as augmented expression of M2-associated genes.…”
Section: Preconditioning-based Modulationmentioning
confidence: 99%
“…Interestingly, microglia can switch their phenotype under different microenvironments. In a variety of neurological disorders, suppression of microglia M1 polarization and promotion of M2 microglia could effectively reduce acute brain injuries and improve neurological outcomes (9)(10)(11). Thus, modulating microglia M1/M2 polarization might be a feasible method to mitigate EBI.…”
Section: Introductionmentioning
confidence: 99%